GENDER DISCRIMINATION ISSUES IN THE LABOUR MARKET OF ARMENIA (World Science, 2018)
Unfortunately, gender stereotypes still remain in the 21st century and require social, cultural, traditional and political radical changes. Often, this inequality is conditioned not by the laws set by the state, but by the so-called "unwritten" laws that are subject to "compulsory enforcement" and have stronger grounds than supreme legislation. Gender inequality is particularly obvious in low-income countries and extremely poor households. The aim of the research is to study and analyze gender discrimination, management and decision-making processes related to education, employment, unemployment, pension security and women's work motivation in labour market policies in the Republic of Armenia. The information of this study was obtained through various secondary sources like statistic reports, websites, besides has been used qualitative research method in particular, the depth interview method.